Sustainable concrete production with recycled concrete wash water beneficiated with CO2 - Sean Monkman; Vincent Meyer (Acta Polytechnica CTU Proceedings)
A significant amount of wastewater is generated through the cleaning of equipment utilized within the ready mixed concrete production cycle. The reuse of concrete wash water as mix water is limited by the negative material performance impacts associated with the suspended solids; the effects are exacerbated with increasing solids contents and water aging. A novel carbon dioxide treatment to allow the use of high solids wash water (specific gravity 1.10) as mix water was examined. Seven batches of concrete were produced and compared: a reference mix, two batches with untreated wash water and four batches with CO2 treated wash water. The carbon dioxide treatment mineralized CO2 at 28% by mass of the treated solids. Acceptable concrete was produced through adjusting admixtures for workability. The compressive strength at 1, 7, 28 and 56 days was improved relative to both the reference and the concrete produced with untreated wash water. The suspended solids containing mineralized CO2 served as a viable cement replacement. The avoided cement and bound carbon dioxide served to lower the carbon impact of the concrete by about 14%. The approach allows three waste streams (CO2, wash water and wash water solids) to be reused to produce more sustainable concrete.